Acute coronary syndrome in clinical practice: gender specifics of risk levels, treatment, and outcomes: RECORD Registry results - A. D. Erlikh; I. I. Shevchenko; D. V. Alekseev; N. A. Gratsianskyi (Кардиоваскулярная терапия и профилактика)
Aim. To compare the clinical characteristics, in-hospital treatment, and treatment outcomes in men and women included in the independent Russian RECORD Registry of acute coronary syndrome (ACS) (n=796; 57,2% men and 42,8% women). Material and methods. The Registry covered 2007–2008 and included 18 clinical hospitals in 13 Russian cities. The mean age of male participants was 60,6±11,3 years; the proportion of the patients aged ≥65 years was 32,3%. Female participants were significantly older, with the majority of women being 65 years or older (66,6% vs. 32,3% of those aged below 65 years; p<0,001). Results. The analysis of anamnestic data demonstrated that in women, pre-existing cardiovascular disease (CVD) and risk factors were significantly more prevalent, while percutaneous coronary intervention (PCI) was significantly less prevalent, compared to men. Women were more often admitted to “non-invasive” hospitals, and at admission, they more often demonstrated Killip class ≥II and higher risk levels. During hospitalization, women were less likely to be administered clopidogrel or new-generation heparins, but more often received diuretics and aldosterone antagonists. Invasive procedures were performed significantly less often in women vs. men. In women and men with ACS and ST segment elevation, in-hospital rates of fatal outcomes were 25,7% and 10,3%, respectively (p=0,003), while for ACS without ST segment elevation, the respective figures were 4,2% and 1,6% (p=0,12). In “invasive” hospitals, the combined incidence of death or myocardial infarction among patients with ACS without ST segment elevation was significantly higher in women (9,9% vs. 3,5% in men; p=0,045). Conclusion. A relatively worse prognosis in female patients included in the RECORD Registry was explained by a higher prevalence of pre-existing CVD and an inadequate treatment, with poor compliance to modern clinical guidelines.